Daily activity patterns of Mohave ground squirrels in a camera trapping study - Barbara M. Leitner; Philip Leitner (California Fish and Wildlife Journal)
We conducted a regional camera trapping study in 2021 to assess the distribution of the Mohave ground squirrel (Xerospermophilus mohavensis; MGS) that resulted in 2,754 detection events. Here we analyze temporal and environmental factors influencing MGS activity, as well as some aspects of our methodology. During 8-day operational periods in two sessions at 55 study sites (total n = 550 cameras), first detections of MGS at individual cameras were most numerous on days 1 and 2, but first detections continued through Day 8 during both sessions. On a daily basis, 99% of all MGS detections began at least 2 hours after sunrise and 98% ended at least 1 hour before sunset. Temperatures recorded by unsheltered trail cameras were an unreliable measure of shaded air temperature. However, data from two weather stations were comparable over a large area and were adjusted based on elevation to estimate air temperatures at nearby study sites. MGS detections were numerous during the warmest daily temperatures throughout the study, underscoring the importance of closing live-traps during warm weather to ensure animal safety. Detections were lower on relatively cool days, especially in early spring. Collectively, these results illustrate the critical importance of ambient temperature to MGS activity patterns and, by extension, their energy budget. Although no comparisons showed significant differences, a test of bait presentation suggested that peanut butter had no particular benefit as an MGS attractant. Activity patterns demonstrate that bait tubes are effective attractants for at least one week. Although MGS activity at cameras can be quantified in various ways, the most comparable metric across investigations is simply presence or absence.